Acute pancreatitis and pneumonia due to Mycoplasma pneumoniae: a case report. (December 2016) - Benzaquen, Michael; Lebowitz, Dan; Belenotti, Pauline; Durand, Jean-Marc; Serratrice, Jacques
Abstract Background Mycoplasma pneumoniae is a bacterium responsible for 15 to 40 % of acute community-acquired pneumonia in children and 20 % of adult cases. Several extrapulmonary manifestations have been reported. We report a rare case of an adult patient suffering from pneumonia associated with an acute pancreatitis in the setting ofMycoplasma pneumoniae infection. Case presentation A 28-year-old Caucasian woman was referred for anorexia lasting for 1 week. Her past medical history was notable for congenital hydrocephalus with consecutive ventriculo-peritoneal shunt, epilepsia and paraparesis. The patient rapidly deteriorated, presenting with dyspnea, tachypnea, productive cough, abdominal pain, and onset of fever. C-reactive protein was at 270 mg/L, with a rise in serum lipase (670 UI/L, N: 13–60). A computed-tomography scan showed an acute interstitial edematous pancreatitis without necrosis, consistent with grade C on the Balthazar score. Thoracic sections revealed diffuse parenchymal consolidations combined with ground glass opacities. Calcium and triglyceride levels were normal. There was no history of recent trauma, alcoholic intake or drug intoxication.Mycoplasma pneumoniae serological assay showed an elevated IgM titer (22 UA/mL), compatible with recent infection, and cold agglutinins were present. A diagnosis of acute pancreatitis and diffuse interstitial pneumonia caused by an infection withMycoplasma pneumoniae was considered. Respiratory and abdominal evolution was quickly favorable after initiation of clarithromycin 500 mg bid. Conclusions The relationship betweenMycoplasma pneumoniae infection and acute pancreatitis has been debated in the literature for many years. This observation, supported by clinical, biological and radiological features, is an additional argument in favor of a non-fortuitous association.